Quantitative diffusion MRI biomarkers predict adverse maternal outcomes in placenta accreta spectrum disorders - Lu, Tao; Wang, Li; Huang, Yufu; Chen, Yazheng; Li, Mou (Frontiers in Medicine, 2025)
IntroductionThis study aimed to investigate the potential of diffusion-weighted imaging (DWI) parameters in predicting adverse maternal outcomes in high-risk patients with placenta accreta spectrum (PAS) disorders.MethodsWe conducted a prospective analysis of 109 patients with PAS, including 15 who experienced adverse maternal outcomes and 94 who did not. All patients underwent DWI, including intravoxel incoherent motion (IVIM) and diffusion kurtosis imaging (DKI). The measured parameters included the apparent diffusion coefficient (ADC), pure diffusion coefficient (D), pseudo-diffusion coefficient (D*), perfusion fraction (f), mean kurtosis (MK), and mean diffusivity (MD). These parameters were compared between the two groups. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to evaluate the diagnostic performance of DWI parameters in predicting adverse maternal outcomes.ResultsPatients with adverse maternal outcomes exhibited significantly higher MD, D, and D* values but significantly lower MK values (p < 0.05). A multivariate regression analysis identified D and the number of prior cesarean deliveries (CDs) as independent predictors of adverse outcomes. The combination of these two factors yielded the highest predictive performance, with an area under the curve (AUC) of 0.766 (95% confidence interval: 0.654–0.878).DiscussionDWI parameters demonstrated a significant association with adverse maternal outcomes in high-risk PAS patients. The combination of prior CD history and the D parameter may serve as a valuable predictive tool for identifying patients at an increased risk of complications.